Anthropogenic nitrogen is changing the East China and Yellow seas from being N deficient to being P deficient. Issue 3 (1st December 2020) - Moon, Ji‐Young; Lee, Kitack; Lim, Weol‐Ae; Lee, Eunil; Dai, Minhan; Choi, Yang‐Ho; Han, In‐Seong; Shin, Kyoungsoon; Kim, Ja‐Myung; Chae, Jinho
Abstract: Addition of the increased anthropogenic nitrogen (NOx and NHy ) emitted from northeast Asian countries to the Yellow and East China seas and coastal waters around Korea has resulted in an unparalleled increase in the nitrate (N) concentration relative to the phosphate (P) and silicate (Si) concentrations in the upper ocean. We found that for the Yellow Sea the increase in N over P was largely explained by increased atmospheric nitrogen deposition, whereas for the northern East China Sea, downstream of the Changjiang River plume, the trend in N increase relative to P was more associated with a change in the combined input of nutrients from atmospheric deposition and riverine discharges. In contrast, the dynamics of the N to P relationship in the southern East China Sea was largely controlled by a change in the intrusion intensity of the Kuroshio Current, which has a low N : P ratio. The disproportionate and persistent input of nutrients to the marine waters of this region over the past four decades has transformed extensive areas from being N deficient to being P deficient, and has concurrently decreased the concentration of Si relative to N. In coastal waters around Korea in particular, these shifts in the nutrient regime have been accompanied by a change from diatom‐dominated to dinoflagellate‐dominated blooms. Given the complexity of coastal ecosystems, the associations between changes in nutrient regimes and biological changes need to be investigated in other coastal areas receiving increasing loads of anthropogenic nitrogen.